Numerical Study of Turbulent Forced Convection in a Square Duct with Discrete X-V Inducing Turbulators (DXVIT) - Amnart Boonloi; Withada Jedsadaratanachai (Energies, 2025)
This research is an extension study that applies a vortex generator previously developed and tested under laminar flow conditions to investigate its performance under turbulent flow conditions, covering the operating range of various heat exchanger systems. This type of vortex generator is called the discrete X-V inducing turbulator (DXVIT), which is derived from the V-baffle, known for its high heat transfer enhancement efficiency, combined with the structure of an orifice that provides durability and stability when installed in heat exchanger systems. The DXVIT is installed to modify the primary flow structure and disrupt the thermal boundary layer (ThBL), resulting in an increase in the convective heat transfer coefficient. This study examines the effects of DXVIT size, installation spacing, flow direction, and DXVIT type on the heat transfer and flow behavior under turbulent flow conditions with Reynolds numbers ranging from 3000 to 16,000. The investigation is conducted using numerical simulation methods. The results are presented in terms of flow and heat transfer behavior, along with an analysis of thermal performance using dimensionless parameters. The findings indicate that the heat transfer rate increases up to 5.29 times, and the thermal performance factor reaches 2.65 under the same pumping power conditions.
Keywords: Heat Transfer Mechanisms; Heat Transfer and Optimization; Fluid Dynamics and Turbulent Flows